Peran Orang Tua Dalam Pembentukan Karakter Anak Sejak Usia Dini Melalui Pendidikan Multikultural - Rina, Rina (ILJ: Islamic Learning Journal, 2025)
Character education in early childhood is crucial for shaping good personality and appreciating diversity. This journal aims to analyze the role of parents in character formation through a multicultural education approach. The research method used is descriptive qualitative, with data collection techniques including interviews, observations, and document studies. The results indicate that parents play an important role in instilling values of tolerance, honesty, and appreciation for differences through modeling and habituation. However, there are obstacles such as external environmental influences and a lack of understanding among parents about multicultural education.